(.5x+5)-1=-.3(3x-4)

Simple and best practice solution for (.5x+5)-1=-.3(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (.5x+5)-1=-.3(3x-4) equation:


Simplifying
(0.5x + 5) + -1 = -0.3(3x + -4)

Reorder the terms:
(5 + 0.5x) + -1 = -0.3(3x + -4)

Remove parenthesis around (5 + 0.5x)
5 + 0.5x + -1 = -0.3(3x + -4)

Reorder the terms:
5 + -1 + 0.5x = -0.3(3x + -4)

Combine like terms: 5 + -1 = 4
4 + 0.5x = -0.3(3x + -4)

Reorder the terms:
4 + 0.5x = -0.3(-4 + 3x)
4 + 0.5x = (-4 * -0.3 + 3x * -0.3)
4 + 0.5x = (1.2 + -0.9x)

Solving
4 + 0.5x = 1.2 + -0.9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.9x' to each side of the equation.
4 + 0.5x + 0.9x = 1.2 + -0.9x + 0.9x

Combine like terms: 0.5x + 0.9x = 1.4x
4 + 1.4x = 1.2 + -0.9x + 0.9x

Combine like terms: -0.9x + 0.9x = 0.0
4 + 1.4x = 1.2 + 0.0
4 + 1.4x = 1.2

Add '-4' to each side of the equation.
4 + -4 + 1.4x = 1.2 + -4

Combine like terms: 4 + -4 = 0
0 + 1.4x = 1.2 + -4
1.4x = 1.2 + -4

Combine like terms: 1.2 + -4 = -2.8
1.4x = -2.8

Divide each side by '1.4'.
x = -2

Simplifying
x = -2

See similar equations:

| 3(3u+2v)-3(4u-3v)= | | 4x^2+29x+25=0 | | X^2-Y^2+15X-19Y-6=0 | | 4x^2-25x+19=-2x+4 | | -3x+5-2=x | | 10+10c=3c+3 | | 0=t^2-t-4 | | 3x-5y=-12solvey | | 10+10c=3c+c | | 3n^2-21=2n | | 22.9+3.00= | | 6x-20=3x+13 | | 2r^2-9r=-7 | | -5-t=21 | | 8=10+3x | | 2(2b+10)=12(b-1) | | 15x+8=20+3x | | 4(2x-2y)+5(2y-x)= | | S=2(3.14159)r^2+2(3.14159)rh | | x^2+6x+10=5 | | 9-9a= | | .75x=20 | | -5+3x=-14 | | (lnx+1)(lnx-1)=0 | | -4(r+8)=-55 | | 8x-2(2x-3)=12+2x | | 7-5v=-4v | | 5(2x+1)-3(x-3)=63 | | x^2+19x+65=0 | | -9(-2w+3x-6)= | | 1=-7x | | 40+9-30+2= |

Equations solver categories